Plasticity of conducting polymer dendrites to bursts of voltage spikes in phosphate buffered saline. Issue 4 (1st December 2022) - Scholaert, Corentin; Janzakova, Kamila; Coffinier, Yannick; Alibart, Fabien; Pecqueur, Sébastien
Abstract: The brain capitalizes on the complexity of both its biochemistry for neurons to encode diverse pieces of information with various neurotransmitters and its morphology at multiple scales to route different pathways for neural interconnectivity. Conducting polymer dendrites can show similar features by differentiating between cations and anions thanks to their charge accumulation profile and the asymmetry in their dendriticity that allows projecting spike signals differently. Here, we exploit such mimicry for in materio classification of bursting activity and investigate, in phosphate buffered saline, the capability of such object to sense bursts of voltage pulses of 100 mV amplitude, emitted by a local gate in the vicinity of the dendrite. The dendrite integrates the different activities with a fading memory time window that is characteristic of both the polarity of the spikes and the temporality of the burst. By this first demonstration, the 'material-object' definitely shows great potential to be a node halfway between the two realms of brain and electronic communication.